A NARRATIVE REVIEW ADDRESSING THE GAP IN DIABETES DIAGNOSIS: CHALLENGES AND PATHWAYS IN INDIA. - Shankar, Anand (Student's Journal of Health Research Africa, 2023)
Diabetes mellitus, an enduring pathological condition distinguished by heightened levels of blood glucose and changes in metabolic processes, continues to pose a substantial global predicament. The condition may result in significant impairment to essential bodily systems, encompassing the cardiovascular system, the arteries and veins, optical systems, renal function, and neural pathways. India faces a substantial burden due to diabetes, fuelled by unhealthy lifestyles and genetic factors unique to its population. Rapid urbanization and economic development of the nation have led to unhealthy lifestyle changes, contributing to a surge in obesity and metabolic disorders, particularly diabetes. In India, undiagnosed cases are prevalent, driven by limited healthcare access and awareness, resulting in delayed care. Despite an alarmingly high prevalence rate, over 50% of diabetes cases remain undiagnosed, straining the healthcare system. In addition to this, treatment and management of diabetes pose further challenges from inadequate infrastructure, workforce shortages, overcrowding, and financial constraints. Not only this, but among diabetic people, non-compliance of medications and variations in treatment strategies, further hinder its management. Thus, there is an imperative need for effective strategies to address these challenges which will overall reduce the burden on the healthcare system and importantly help the nation to tackle diabetes. The objective of the review paper is to highlight the substantial burden of diabetes mellitus in India, focusing on the challenges it presents to healthcare systems and the population. The paper aims to emphasize the need for effective strategies to address these challenges and reduce the burden of diabetes on the healthcare system and the nation as a whole. By taking comprehensive steps, India can offer accessible, efficient, and quality healthcare, ultimately alleviating the burden of preventable diseases and deaths.